2016
DOI: 10.1093/molbev/msw009
|View full text |Cite
|
Sign up to set email alerts
|

Indispensability of Horizontally Transferred Genes and Its Impact on Bacterial Genome Streamlining

Abstract: Why are certain bacterial genomes so small and compact? The adaptive genome streamlining hypothesis posits that selection acts to reduce genome size because of the metabolic burden of replicating DNA. To reveal the impact of genome streamlining on cellular traits, we reduced the Escherichia coli genome by up to 20% by deleting regions which have been repeatedly subjects of horizontal transfer in nature. Unexpectedly, horizontally transferred genes not only confer utilization of specific nutrients and elevate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 60 publications
6
80
0
3
Order By: Relevance
“…In addition, the mode of growth decrease was nutritional dependent. In comparison to a continuous gradual decrease in the poor condition (M63), a stepwise decrease in the rich condition (LB) was detected, close to the finding reported recently 26 . The variation in mode of growth decrease reflected the degree of requirement of dispensable genomic sequences for efficient growth.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, the mode of growth decrease was nutritional dependent. In comparison to a continuous gradual decrease in the poor condition (M63), a stepwise decrease in the rich condition (LB) was detected, close to the finding reported recently 26 . The variation in mode of growth decrease reflected the degree of requirement of dispensable genomic sequences for efficient growth.…”
Section: Resultssupporting
confidence: 88%
“…Rough measurements of a series of reduced genomes (constructed from W3110) have not indicated any significant differences in the growth rate on the basis of optical density (OD), 14 whereas a closely related study has reported increased cell division time in another reduced genome library (constructed from MG1655) 32 . In addition, the well-known “clean” genome (MDS42) 12 has a growth rate comparable to that of its parent wild type genome (MG1655) in minimal medium, 22 , 33 and no general trend has been observed between genome size and growth in rich medium 26 . Whether and how the genome reduction links to the bacterial growth is still in argument, due to the different thinking on growth cost and/or genome evolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli, with its large Ne is very sensitive to small selective differences caused by mutations in its genes. This includes transcriptional and translational selection 20 , as well as selection for function 21 and the cost of maintenance 22 . Not all organisms have very large Ne, however.…”
Section: Text Box 1 -Small Selective Pressuresmentioning
confidence: 99%
“…There is a growing body of evidence that accessory genes might provide significant benefit 21,36 . Karcagi and co-workers analysed a range of E. coli genomes at different levels of gene deletion, specifically genes that had been recently acquired by HGT 21 . They found that HGT genes conferred significant benefits in terms of substrate utilisation, efficiency of resource usage to build new cells, and tolerance to stress.…”
Section: An Adaptive Modelmentioning
confidence: 99%